Tunnel type sodium manganate material as well as preparation method and application thereof

By using small particles K0.5MnO2 as the precursor to perform ion exchange preparation, the problems of harsh conditions and poor electrochemical performance in the preparation process of existing tunnel-type sodium manganate materials were solved, and efficient and stable nanorod-shaped tunnel-type sodium manganate materials were successfully prepared.

CN119569125APending Publication Date: 2025-03-07SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311120770.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing preparation methods for tunnel-type sodium manganate materials have problems such as harsh conditions, complex processes, high production costs, and the prepared sodium manganate particles are prone to agglomeration, varying sizes, and poor electrochemical performance.

Method used

Small particles K0.5MnO2 are used as the precursor, and ion exchange is performed with sodium source to form phases, and excess sodium salt is washed away by water and ethanol to prepare a nanorod-shaped tunnel-type sodium manganate material.

Benefits of technology

The tunnel-type sodium manganate material produced is not agglomerated, has a high crystallinity, has a moderate and adjustable aspect ratio, which is suitable for the coordinated transportation of ions and electrons, and improves the rate performance and cycle stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569125A_ABST
    Figure CN119569125A_ABST
Patent Text Reader

Abstract

The invention relates to a tunnel type sodium manganate material as well as a preparation method and application thereof. The tunnel-type sodium manganate material is in a nanorod shape, and the diameter of the tunnel-type sodium manganate material is 50 nm to 10 [mu] m, preferably 200 nm to 500 nm; the length is 0.1 mu m to 50 mu m, preferably 1 mu m to 10 mu m; the chemical composition is Na < 0.44-x > KxMnO2, x is more than or equal to 0 and less than or equal to 0.2, and preferably, x is more than or equal to 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material preparation, and specifically relates to a tunnel-type sodium manganate nanorod material and an ion exchange preparation method and application thereof. Background Art

[0002] Tunnel type sodium manganate (Na 0.44 MnO2) material is a three-dimensional sodium storage material with a large one-dimensional pore structure. In the tunnel-type sodium manganate structure, manganese-oxygen polyhedrons are connected by common edges to form double or triple linear chains parallel to each other. These chains constitute the manganese structure framework and form large pores, which can accommodate the insertion and removal of sodium ions. This unique crystal structure gives it excellent properties, such as high ionic conductivity and high stability, making it suitable as a sodium storage positive electrode and has great application potential in energy storage. From the perspective of stability, compared with other positive electrodes such as two-dimensional layered oxides, tunnel-type sodium manganate is highly stable to air and water, and will not deteriorate due to long-term contact with air and water. It is easy to produce and store on a large scale, and has extremely high application value in aqueous sodium storage systems. From an electrochemical perspective, the unique large pore structure of tunnel-type sodium manganate is suitable for the rapid insertion and extraction of sodium ions, making it a capacitive sodium ion storage. At the same time, its three-dimensional framework can reduce the volume change caused by the insertion and extraction of sodium ions. It has excellent rate performance and cycle stability, which is better than the common layered oxide positive electrode. It has broad application prospects in fast charging batteries and sodium ion capacitors. At the same time, compared with the related materials currently widely used in the above applications, the preparation conditions of tunnel-type sodium manganate are loose, no strict atmosphere is required, the preparation cost is relatively low, the toxicity is low, it is safe and stable, and the harm to the environment is small.

[0003] At present, tunnel-type sodium manganate materials are mainly prepared by high-temperature solid-phase synthesis, sol-gel method and molten salt method, and tunnel-type sodium manganate with different morphological characteristics can be prepared by controlling the synthesis conditions and post-treatment, which has broad application prospects in the field of sodium-ion batteries and supercapacitors. Patent KR101613435B1 discloses a solid-phase synthesis method for tunnel-type sodium manganate materials, which uses KMnO4 to synthesize Mn2O3 and then reacts with Na2CO3 to synthesize tunnel-type sodium manganate, without the step of molten salt ion exchange. In addition, there is a document that discloses the use of a molten salt method to synthesize tunnel-type sodium manganate materials using sodium carbonate, manganese oxide and sodium chloride as raw materials, without K 0.5 MnO2 precursor. 0.5 MnO2 is used as a precursor, and a tunnel-type sodium manganate material is prepared by ion exchange with a sodium source. However, the current preparation method of tunnel-type sodium manganate material often has the disadvantages of harsh conditions, complex preparation process, and high production cost. The prepared sodium manganate particles also have the disadvantages of easy agglomeration, uneven size, and poor electrochemical performance. Summary of the invention

[0004] In view of the above technical problems, the present invention adopts small particles K 0.5 A method for preparing tunnel-type sodium manganate using MnO2 as a precursor, ion exchange with a sodium source, and washing away excess sodium salt with water and ethanol. Compared with the liquid phase method and the traditional high-temperature solid phase synthesis method, the tunnel-type sodium manganate produced by the ion exchange preparation method does not agglomerate, has high crystallinity, and has a nanorod-like morphology, with a moderate and controllable aspect ratio, which is conducive to the coordinated transport of ions and electrons; in addition, some residual potassium ions can expand the pores, facilitate the transmission of sodium ions, and have high rate performance and cycle stability.

[0005] In the first aspect, the present invention provides a tunnel-type sodium manganate material, wherein the tunnel-type sodium manganate material is in the shape of a nanorod, with a diameter of 50nm to 10μm, preferably 200nm to 500nm; a length of 0.1μm to 50μm, preferably 1μm to 10μm; and a chemical composition of Na 0.44-x K x MnO2, wherein 0≤x≤0.2, preferably 0≤x≤0.03.

[0006] Preferably, the capacity of the tunnel-type sodium manganate material at 0.2C is 90 to 150 mAh g -1 , preferably 110~122mAh g -1 ; The capacity at 20C is 20~90mAh g -1 , preferably 65~85mAh g -1 The capacity retention rate after 200 cycles at 0.5C is 50% to 100%, preferably 90% to 99%; the capacity retention rate after 900 cycles at 20C is 50% to 100%, preferably 95% to 99%.

[0007] In a second aspect, the present invention provides a method for preparing the tunnel-shaped sodium manganate material, the method comprising the following steps: mixing potassium source powder and manganese source powder and performing a first calcination to obtain K 0.5 MnO2 precursor, and then the K 0.5 The MnO2 precursor is mixed with the sodium source powder and calcined for the second time to cause ion exchange, and then soaked in deionized water, filtered, washed and dried to obtain the tunnel-type sodium manganate material.

[0008] Preferably, the potassium source powder is selected from at least one of potassium carbonate, potassium bicarbonate, potassium hydroxide and potassium oxide; preferably, the particle size of the potassium source powder is 10 to 50 μm; the manganese source powder is selected from at least one of manganese trioxide, manganese tetraoxide, manganese dioxide and manganese carbonate; preferably, the particle size of the manganese source powder is 200 nm to 10 μm; The molar ratio of potassium in the potassium source powder to manganese in the manganese source powder is controlled to be 0.45 to 0.55.

[0009] Preferably, the heating rate of the first calcination is 2-10°C / min, the calcination temperature is 500-1000°C, preferably 700-800°C, the calcination time is 2-48h, preferably 6-8h, and the cooling rate is 1-300°C / min, and the mixture is cooled to room temperature.

[0010] Preferably, the sodium source powder is selected from at least one of sodium chloride, sodium bromide, sodium iodide and sodium nitrate; preferably, the particle size of the sodium source powder is 10 to 200 μm; Control the sodium in the sodium source powder and the precursor K 0.5 The molar ratio of MnO2 is 0.45-10.

[0011] Preferably, the heating rate of the second calcination is 2-10°C / min, the calcination temperature is 700-1000°C, preferably 750-850°C, the calcination time is 2-48h, preferably 4-6h, the cooling rate is 1-300°C / min, and it is naturally cooled to room temperature.

[0012] Preferably, the deionized water soaking temperature is 10-70° C., and the soaking time is 1-600 min.

[0013] In a third aspect, the present invention provides an application of the above-mentioned tunnel-type sodium manganate material in sodium ion battery positive electrode materials and supercapacitors.

[0014] Beneficial Effects The present invention adopts a high-temperature molten salt ion exchange method under atmospheric conditions to prepare tunnel-type sodium manganate, which has a simple preparation process, is easy to control, and has low cost. The grown tunnel-type sodium manganate is pure and free of impurities, and is easy to mass produce. The tunnel-type sodium manganate material obtained by the preparation method provided by the present invention has excellent rate performance and cycle stability, excellent electrochemical performance, good air stability, low preparation cost, and is suitable for the field of sodium ion battery positive electrode materials and supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 K prepared in Example 1 of the present invention 0.5 XRD diffraction pattern of MnO2 precursor powder; Figure 2 K prepared in Example 1 of the present invention 0.5 SEM image of MnO2 precursor powder; Figure 3 The tunnel-type sodium manganate Na prepared in Example 1 of the present invention 0.435 K 0.005MnO2 powder XRD diffraction pattern; Figure 4 The tunnel-type sodium manganate Na prepared in Example 1 of the present invention 0.435 K 0.005 SEM image of MnO2; Figure 5 The tunnel-type sodium manganate Na prepared in Example 1 of the present invention 0.435 K 0.005 XPS spectrum of MnO2; Figure 6 The tunnel-type sodium manganate Na prepared in Example 1 of the present invention 0.435 K 0.005 Rate performance diagram of MnO2; Figure 7 The tunnel-type sodium manganate Na prepared in Example 1 of the present invention 0.435 K 0.005 Cyclic performance test diagram of MnO2; Figure 8 The solid phase method for synthesizing tunnel-type sodium manganate Na in Comparative Example 1 of the present invention is as follows: 0.44 SEM image of MnO2; Fig. 9 The solid phase method for synthesizing tunnel-type sodium manganate Na in Comparative Example 1 of the present invention is as follows: 0.44 Rate performance diagram of MnO2. DETAILED DESCRIPTION

[0016] The present invention is further described by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, rather than to limit the present invention.

[0017] First, the present invention provides a tunnel-type sodium manganate material. The tunnel-type sodium manganate material is in the shape of a nanorod, with a diameter of 50nm to 10μm, preferably 200nm to 500nm; a length of 0.1μm to 50μm, preferably 1μm to 10μm; and a chemical composition of Na 0.44-x K x MnO2, wherein 0≤x≤0.2, preferably 0≤x≤0.03.

[0018] The electron transfer rate of traditional granular materials is much greater than the ion transfer rate, and ion transfer drags down electron transfer, resulting in a slow overall reaction rate and poor rate performance. The rod-shaped tunnel-type sodium manganate provided by the present invention has an ion transfer rate (radial) that is equivalent to an electron transfer rate (axial), which can greatly increase the reaction rate, thereby having a more excellent rate performance. At the same time, if the diameter and length are too large, the transmission distances of ions and electrons will be longer, and the rate performance of the material will be reduced; if the diameter and length are too small, the specific surface area of ​​the material will increase, the surface side reactions will intensify, and the cycle performance will be seriously reduced. In addition, the sodium manganate material with an x ​​value that is too large cannot form a pure tunnel phase, and will contain a large amount of unreacted precursors, which will also cause a serious decline in material performance.

[0019] The tunnel-type sodium manganate material provided by the present invention is 0.2C (1C = 120mA g -1 ) is 90~150mAhg -1 , preferably 110~122mAh g -1 ; The capacity at 20C is 20~90mAh g -1 , preferably 65~85mAh g -1 The capacity retention rate after 200 cycles at 0.5C is 50% to 100%, preferably 90% to 99%; the capacity retention rate after 900 cycles at 20C is 50% to 100%, preferably 95% to 99%.

[0020] The following is an exemplary description of the preparation method of the tunnel-type sodium manganate material provided by the present invention. The preparation method may include the following steps: mixing potassium source powder and manganese source powder and performing a first calcination to obtain K 0.5 MnO2 precursor, and then the K 0.5 The MnO2 precursor is mixed with the sodium source powder and calcined for the second time to cause ion exchange, and then soaked in deionized water, filtered, washed and dried to obtain the tunnel-type sodium manganate material.

[0021] In some embodiments, the potassium source powder can be selected from at least one of potassium carbonate, potassium bicarbonate, potassium hydroxide, and potassium oxide; preferably, the particle size of the potassium source powder can be controlled to be 10 to 50 μm. Too small a particle size will result in high cost, while too large a particle size will result in low reaction activity, longer ball milling and calcination time, and easy to cause the precursor to be impure.

[0022] In some embodiments, the manganese source powder can be selected from at least one of manganese trioxide, manganese tetraoxide, manganese dioxide, and manganese carbonate; preferably, the particle size of the manganese source powder can be controlled to be 200nm to 10μm. Too small a particle size will result in high cost, while too large a particle size will result in low reaction activity, too long a ball milling and calcination time, and thus an impure precursor.

[0023] In some embodiments, the potassium source powder and the manganese source powder may be mixed and ball-milled using a high-energy ball mill; preferably, the ball-milling speed may be 100 to 500 rpm, and the ball-milling time may be 2 to 4 hours.

[0024] In some embodiments, the molar ratio of potassium in the potassium source powder to manganese in the manganese source powder is controlled to be 0.45 to 0.55. Controlling the molar ratio of the two within this range can promote the synthesis of tunnel phase sodium manganate nanorod materials. If the molar ratio is too small or too large, pure tunnel phase sodium manganate nanorod materials cannot be generated. If the molar ratio is too small, unreacted manganese source impurities will appear in the material. If the molar ratio is too large, layered phase sodium manganate particles will be generated.

[0025] In some embodiments, the first calcination can be carried out in a muffle furnace, the heating rate can be controlled at 2-10°C / min, the calcination temperature can be 500-1000°C, preferably 700-800°C, the calcination time can be 2-48h, preferably 6-8h, the cooling rate can be 1-300°C / min, and cooled to room temperature. Controlling the calcination temperature within this special range can promote the formation of K 0.5 MnO2 pure phase precursor with good particle size and crystallinity. At the same time, too short calcination time will lead to incomplete reaction and impure precursor; too long calcination time will increase cost.

[0026] In some embodiments, the sodium source powder can be selected from at least one of sodium chloride, sodium bromide, sodium iodide, and sodium nitrate; preferably, the particle size of the sodium source powder can be controlled to be 10 to 200 μm. The selection of sodium source powder is preferably a low melting point neutral sodium salt, preferably with a melting point below 850°C. The use of alkaline sodium salts (such as sodium acetate, sodium oxalate, sodium carbonate, etc.) is likely to result in impure products and the appearance of layered sodium manganate particles. The use of sodium salts with too high a melting point (such as NaF) is not easy to melt, the reaction temperature required is too high, impurities are easily generated, and the size of the nanorods is difficult to control. At the same time, too small a particle size of the sodium source powder will result in excessively high costs, and too large a particle size will result in low reaction activity, difficulty in melting, and a long time for ball milling and calcination, resulting in a decrease in product purity and difficulty in cleaning.

[0027] In some embodiments, the sodium source powder and the precursor K 0.5 The MnO2 mixture can be ball-milled using a high-energy ball mill; preferably, the ball-milling speed can be 100 to 500 rpm, and the ball-milling time can be 2 to 4 hours.

[0028] In some embodiments, the sodium in the sodium source powder and the precursor K can be controlled. 0.5The molar ratio of MnO2 is 0.45 to 10. Controlling the molar ratio of the two within this specific range can ensure the potassium content (i.e., x value) in the exchange product. A molar ratio that is too low will result in x being too large and unreacted precursor residues, significantly reducing the material capacity and rate performance; a molar ratio that is too high will result in x being too small, thus failing to reach K + The purpose of enlarging the sodium ion transport channel is to expand the size of the nanorods, and the rate performance is poor.

[0029] In some embodiments, the second calcination can be carried out in a muffle furnace, the heating rate can be controlled to be 2-10°C / min, the calcination temperature can be 700-1000°C, preferably 750-850°C, the calcination time can be 2-48h, preferably 4-6h, the cooling rate can be 1-300°C / min, and it is naturally cooled to room temperature. Controlling the calcination temperature within the above-mentioned specific range can promote the formation of tunnel phase sodium manganate. Too high or too low a calcination temperature cannot form a pure phase. The selection of specific temperature can be based on different sodium source melting points to ensure that the calcination temperature is above the corresponding sodium source melting point. The product obtained within the calcination temperature is moderate in size and has better rate performance. At the same time, too short a calcination time will result in incomplete reaction and failure to form a pure phase; too long a calcination time will result in excessively large material particle size and decreased rate performance.

[0030] In some embodiments, the temperature of the deionized water soaking can be 10 to 70° C., and the soaking time can be 1 to 600 min. Soaking in deionized water can promote the removal of excess unreacted sodium source and potassium salt byproducts (KCl, etc.) produced by the exchange. If the soaking temperature is too low or the soaking time is too short, it will be difficult to wash away the unreacted sodium source and the exchange byproducts; if the soaking temperature is too high or the soaking time is too long, the deionized water will enter the tunnel-type sodium manganate lattice, causing the structure to change, and its capacity and rate performance will be significantly reduced.

[0031] In some embodiments, the washing may be performed using deionized water and ethanol.

[0032] The invention adopts a high-temperature molten salt ion exchange method under atmospheric conditions to prepare tunnel-type sodium manganate, has a simple preparation process, is easy to control the process, does not require atmosphere, has low cost, and the grown tunnel-type sodium manganate is pure and free of impurities, and is easy to mass produce.

[0033] The tunnel-type sodium manganate material obtained by the preparation method provided by the present invention has excellent rate performance and cycle stability, excellent electrochemical performance, good air stability, low preparation cost, and is suitable for the field of sodium ion battery positive electrode materials and supercapacitors.

[0034] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0035] Example 1

[0036] The preparation method of the tunnel-type sodium manganate material provided by the present invention is as follows: (1) Potassium carbonate and manganese trioxide were milled in a high-energy ball mill at a potassium-manganese molar ratio of 0.5 at a speed of 400 rpm for 4 h, and then placed in a muffle furnace for calcination at 800° C. for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain K 0.5 MnO2 precursor. Among them, the K 0.5 The corresponding XRD diffraction pattern and SEM photo of MnO2 precursor are shown in Figure 1 and 2 shown. (2) Sodium chloride and K prepared in step (1) 0.5 The MnO2 precursor was placed in a high-energy ball mill with a molar ratio of 1.25, ball-milled at 400 rpm for 4 hours, and then placed in a muffle furnace for calcination at 805°C for 4 hours. The product was naturally cooled to room temperature, and then soaked in 50°C deionized water for 30 minutes and filtered. The product was washed with deionized water and ethanol three times and dried at 60°C for 4 hours to obtain a tunnel-type sodium manganate material with a chemical composition of Na 0.435 K 0.005 MnO2. Wherein, the XRD diffraction pattern and scanning electron microscope photo of the tunnel-type sodium manganate material are as follows: Figure 3 and 4 As shown in the figure, the tunnel-type sodium manganate Na 0.435 K 0.005 The diameter of MnO2 is 200-500nm and the length is 1-10μm. The XPS spectrum of the tunnel-type sodium manganate material is as follows Figure 5 shown.

[0037] A half-cell was assembled with sodium as the negative electrode and the tunnel-type sodium manganate material as the positive electrode for testing. Figure 6 , 7 As shown in the figure, the capacity of the tunnel-type sodium manganate material prepared in Example 1 at 0.2C is 118.7 mAh g -1 , the capacity at 20C is 79 mAh g-1 The capacity retention rate after 200 cycles at 0.5C is 96.3%, and the capacity retention rate after 900 cycles at 20C is 98.1%.

[0038] Example 2

[0039] The preparation method of Example 2 is similar to that of Example 1, with the main difference being that in step (2), the calcination time is 10 h.

[0040] The tunnel-shaped sodium manganate prepared in Example 2 has a diameter of 2 to 5 μm, a length of 10 to 50 μm, and a capacity of 110 mAh g at 0.2C. -1 , the capacity at 20C is 30mAh g -1 .

[0041] Example 3

[0042] The preparation method of this embodiment 3 is similar to that of embodiment 1, except that in step (2), sodium chloride and K prepared in step (1) are used. 0.5 The molar ratio of the MnO2 precursor is 0.6.

[0043] The tunnel-shaped sodium manganate prepared in Example 3 has a diameter of 100-300 nm, a length of 0.5-5 μm, and a capacity of 104 mAh g at 0.2C. -1 , the capacity at 20C is 47 mAh g -1 .

[0044] Example 4

[0045] The preparation method of this embodiment 4 is similar to that of embodiment 1, except that in step (2), sodium chloride and K prepared in step (1) are used as 0.5 The molar ratio of the MnO2 precursor is 5.

[0046] The tunnel-shaped sodium manganate prepared in Example 4 has a diameter of 2-5 μm, a length of 20-50 μm, and a capacity of 116 mAh g at 0.2C. -1 , the capacity at 20C is 45mAh g -1 .

[0047] Example 5

[0048] The preparation method of this Example 5 refers to that of Example 1, with the main difference being that in step (2), the calcination temperature of the muffle furnace is 900°C.

[0049] The tunnel-shaped sodium manganate prepared in Example 5 has a diameter of 2-5 μm, a length of 10-20 μm, and a capacity of 96 mAh g at 0.2C. -1 , the capacity at 20C is 68 mAh g-1 .

[0050] Example 6

[0051] The preparation method of Example 6 is similar to that of Example 1, with the main difference being that in step (1), the manganese source is replaced with manganese dioxide.

[0052] The tunnel-shaped sodium manganate prepared in Example 6 has a diameter of 200-500 nm, a length of 1-10 μm, and a capacity of 114 mAh g at 0.2C. -1 , the capacity at 20C is 71 mAh g -1 .

[0053] Comparative Example 1

[0054] Sodium carbonate and manganese trioxide were milled in a high-energy ball mill at a sodium-manganese molar ratio of 0.5 at 400 rpm for 4 h, and then calcined at 800 °C for 10 h in a muffle furnace. After the reaction was completed, it was naturally cooled to room temperature to obtain Na2O3 synthesized by the solid phase method. 0.44 MnO2 particles.

[0055] Comparative Example 1: Na 0.44 SEM photos of MnO2 particles and rate performance Figure 8 , 9 As shown in the figure, the Na prepared in Comparative Example 1 0.44 The MnO2 particles are significantly agglomerated and have uneven diameters. The capacity at 0.2C is 108 mAh g -1 , the capacity at 20C is 50mAh g -1 .

[0056] Comparative Example 2

[0057] The preparation method of this comparative example 2 refers to that of Example 1, except that in step (2), sodium chloride and K prepared in step (1) are 0.5 The molar ratio of the MnO2 precursor is 0.4.

[0058] The tunnel-type sodium manganate prepared in Comparative Example 2 is not a pure phase and contains a large amount of unreacted precursor particles. The capacity at 0.2C is 95 mAh g -1 , the capacity at 20C is 20mAh g -1 .

[0059] Comparative Example 3

[0060] The preparation method of this comparative example 3 refers to that of Example 1, with the main difference being that in step (2), the calcination time in the muffle furnace is 1 h.

[0061] The tunnel-shaped sodium manganate prepared in this comparative example 3 has a diameter of 10 to 100 nm and a length of 200 nm to 1 μm. The capacity at 0.2C is 104 mAh g -1 , the capacity at 20C is 1.2 mAh g -1 .

[0062] Comparative Example 4

[0063] The preparation method of this comparative example 4 refers to that of Example 1, with the main difference being that after the preparation, a high-energy ball mill is used for ball milling at a rotation speed of 400 rpm for 30 min.

[0064] The tunnel-shaped sodium manganate prepared in Comparative Example 4 is in granular form with a particle size of 10 to 100 nm. The capacity at 0.2C is 84 mAh g -1 , the capacity at 20C is 0.2 mAh g -1 .

[0065] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A tunnel-type sodium manganate material, characterized in that: The tunnel-type sodium manganate material is in the shape of a nanorod, with a diameter of 50nm to 10μm, preferably 200nm to 500nm; a length of 0.1μm to 50μm, preferably 1μm to 10μm; and a chemical composition of Na 0.44-x K x MnO2, wherein 0≤x≤0.2, preferably 0≤x≤0.

03.

2. The tunnel-type sodium manganate material according to claim 1, characterized in that: The capacity of the tunnel-type sodium manganate material at 0.2C is 90 to 150 mAh g -1 , preferably 110~122mAh g -1 ; The capacity at 20C is 20~90mAh g -1 , preferably 65~85mAh g -1 The capacity retention rate after 200 cycles at 0.5C is 50% to 100%, preferably 90% to 99%; the capacity retention rate after 900 cycles at 20C is 50% to 100%, preferably 95% to 99%.

3. A method for preparing the tunnel-type sodium manganate material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: mixing potassium source powder and manganese source powder and performing a first calcination to obtain K 0.5 MnO2 precursor, and then the K 0.5 The MnO2 precursor is mixed with the sodium source powder and calcined for the second time to cause ion exchange, and then soaked in deionized water, filtered, washed and dried to obtain the tunnel-type sodium manganate material.

4. The preparation method according to claim 3, characterized in that: The potassium source powder is selected from at least one of potassium carbonate, potassium bicarbonate, potassium hydroxide, and potassium oxide; preferably, the particle size of the potassium source powder is 10 to 50 μm; the manganese source powder is selected from at least one of manganese trioxide, manganese tetraoxide, manganese dioxide, and manganese carbonate; preferably, the particle size of the manganese source powder is 200 nm to 10 μm; The molar ratio of potassium in the potassium source powder to manganese in the manganese source powder is controlled to be 0.45 to 0.

55.

5. The preparation method according to claim 3 or 4, characterized in that: The heating rate of the first calcination is 2-10°C / min, the calcination temperature is 500-1000°C, preferably 700-800°C, the calcination time is 2-48h, preferably 6-8h, the cooling rate is 1-300°C / min, and the mixture is cooled to room temperature.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The sodium source powder is selected from at least one of sodium chloride, sodium bromide, sodium iodide and sodium nitrate; preferably, the particle size of the sodium source powder is 10 to 200 μm; Control the sodium in the sodium source powder and the precursor K 0.5 The molar ratio of MnO2 is 0.45-10.

7. The preparation method according to any one of claims 3 to 6, characterized in that: The heating rate of the second calcination is 2-10°C / min, the calcination temperature is 700-1000°C, preferably 750-850°C, the calcination time is 2-48h, preferably 4-6h, the cooling rate is 1-300°C / min, and it is naturally cooled to room temperature.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The deionized water soaking temperature is 10-70° C., and the soaking time is 1-600 min.

9. Use of the tunnel-type sodium manganate material according to claim 1 or 2 in a positive electrode material for a sodium ion battery and a supercapacitor.

Citation Information

Patent Citations

  • A manufacturing method of Na0.44MnO2 nano-rod for an electrode and a manufacturing method sodium rechargeable battery thereof

    KR101613435B1